Effect of biochar-amended urea on nitrogen economy of soil for improving the growth and yield of wheat (Triticum Aestivum L.) under field condition. (2nd October 2017) - Abbas, Azhar; Yaseen, Muhammad; Khalid, Muhammad; Naveed, Muhammad; Aziz, Muhammad Zahir; Hamid, Yasir; Saleem, Muhammad
ABSTRACT: A field experiment was conducted to evaluate effect of biochar-amended urea on nitrogen economy of soil for improving the growth and yield of wheat under field condition. Experiment plan was comprised of twelve treatments with four replications including treatments without application of urea and biochar (control) and urea only. Biochar was applied at 1–10% of the weight of urea fertilizer applied each treatment. Results showed that application of biochar at 10% with recommended dose of urea significantly improved plant height, spike length, number of tillers, number of spikelet per spike, 1000 grain weight, grain yields, biomass yield, harvesting index, nitrogen (N) concentration and uptake in grain and straw, and agronomic efficiency of nitrogen by 6.0%, 11.1%, 32.0%, 55.3%, 5.4%, 38.0%, 19.0%, 9.0%, 19.0%, 26.0%, 65.0%, 50.0%, and 63.0%, respectively, as compared to treatment comprised of recommended rate of nitrogen without biochar.